FIVE WELL-BEING DIMENSIONS OF TRAT PEOPLE: A COMMUNITY SELF-MANAGEMENT MODEL FOR SUSTAINABLE DEVELOPMENT - Pantarat Srisuwan (PEOPLE: International Journal of Social Sciences, 2026)
Thailand’s development has long been shaped by a highly centralized administrative structure, which often limits the responsiveness of public policies to local contexts and reduces opportunities for citizens to participate in shaping their own development pathways. This study aims to examine how civil society networks at the local level can strengthen participatory governance and contribute to sustainable social development. The research is part of a broader project on social innovation for strengthening democratic communities within the context of Thai society. Trat Province was selected as the case study due to its strong social capital and active networks of community organizations that are capable of collaborating effectively with government agencies, the private sector, and academic institutions. The study employed a Participatory Action Research (PAR) approach to create collaborative spaces where citizens and network partners jointly analyzed community issues, exchanged knowledge, and developed strategies for local development. The findings reveal that public policy processes in Trat Province have been significantly driven by civic networks, particularly the Trat Community Organization Network, which functions as a coordinating mechanism linking various stakeholders and promoting integrated solutions to community problems. This process operates under the conceptual framework of the “Five Well-Being Dimensions of Trat People,” consisting of health, economy, environment, housing, and social harmony. These dimensions have served as guiding principles for participatory policy development and provincial development strategies. The study demonstrates that strengthening community networks and participatory mechanisms can foster a self-managed province model, reinforcing grassroots democracy and supporting sustainable development.